Clinical Efficacies of the Minimal Retroperitoneal Approach for Infectious Spondylodiscitis: A Clinical Case Series - Tsunehiko Konomi; Shinjiro Kaneko; Amir Fariz Zakaria; Kanehiro Fujiyoshi; Junichi Yamane; Takashi Asazuma; Yoshiyuki Yato (Spine Surgery and Related Research, 2021)
Introduction: An anterior surgical approach for severe infectious spondylodiscitis in the lumbar region is optimal but not always atraumatic. The aim of this study was to evaluate the efficacy and safety of a minimal anterior-lateral retroperitoneal approach, also known as a surgical approach for oblique lumbar interbody fusion, for cases with severe infectious spondylodiscitis with osseous defects. Methods: Twenty-four consecutive patients who underwent anterior debridement and spinal fusion with an autologous strut bone graft for infectious spondylodiscitis with osseous defects were reviewed retrospectively. Eleven patients underwent the minimal retroperitoneal approach (Group M), and 13 underwent the conventional open approach (Group C). Peri- and postoperative clinical outcomes, that is, estimated blood loss (EBL), operative time (OT), creatine kinase (CK) level, visual analog scale (VAS), and rates of bone union and additional posterior instrumentation, were evaluated, and the differences between both groups were assessed statistically. Results: Mean EBL, serum CK on the 1st postoperative day, and VAS on the 14th postoperative day were 202.1 mL, 390.9 IU/L, and 9.5 mm in Group M and 648.3 mL, 925.5 IU/L, and 22.3 mm in Group C, respectively, with statistically significant differences between the groups. There were no statistically significant intergroup differences in OT and rates of bone union and additional posterior instrumentation. Conclusions: Anterior debridement and spinal fusion using the minimal retroperitoneal approach is a useful and safe surgical technique. Although a preponderance of the minimal approach regarding early bone union is not validated, this technique has the advantages of conventional open surgery, but reduces blood loss, muscle injury, and pain postoperatively.